2020
DOI: 10.2217/pgs-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Methadone: A Narrative Review of the Literature

Abstract: Background: Methadone, a synthetic opioid with longer duration of action and lower abuse potential compared with morphine, is used to prevent opioid withdrawal, as well as to manage chronic and acute surgical pain. The variability in response to methadone has been widely recognized. The purpose of this article is to review the literature on the pharmacogenetic factors underlying this variability. Materials & methods: This is a narrative overview of the literature on the genetic variants affecting pharmacod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“… 34 , 35 , 36 , 37 Most of these were not found to be related to the clearances of methadone, contrary prior in vitro and in vivo studies. 38 The CYP2B6 activity score was found to be strongly related to the metabolism of the parent drug to the primary metabolite EDDP for both the enantiomers. The rs11882424, an intronic SNP of CYP2B6 , was previously found to affect the clearance of methadone, although the direction of influence is unclear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 34 , 35 , 36 , 37 Most of these were not found to be related to the clearances of methadone, contrary prior in vitro and in vivo studies. 38 The CYP2B6 activity score was found to be strongly related to the metabolism of the parent drug to the primary metabolite EDDP for both the enantiomers. The rs11882424, an intronic SNP of CYP2B6 , was previously found to affect the clearance of methadone, although the direction of influence is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…CYP2B6, CYP2D6, CYP2C19, CYP3A4, and CYP3A5 were tested using their activity scores as these alleles are well studied and the phenotypic classifications or activity scores are reasonably known for multiple drugs from published literature 34–37 . Most of these were not found to be related to the clearances of methadone, contrary prior in vitro and in vivo studies 38 . The CYP2B6 activity score was found to be strongly related to the metabolism of the parent drug to the primary metabolite EDDP for both the enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…While 516G>T is often considered a canonical CYP2B6 mutation, 58 and may be the only polymorphism routinely assessed in patients or clinical studies, it appears that 983T>C is also a canonical loss of function variant and should also be assessed along with 516G>T if testing is performed.…”
Section: Discussionmentioning
confidence: 99%
“…It is a noncompetitive NMDA antagonist available in a 50:50 racemic mixture of R-and S-methadone. [41][42][43] R-methadone is responsible for methadone's analgesic and therapeutic properties, whereas S-methadone is responsible for most of methadone's adverse reactions. 41 Most studies on the genetic variants affecting pharmacodynamics of methadone were conducted in patients receiving methadone maintenance therapy for OUD.…”
Section: Table 3 (Continued)mentioning
confidence: 99%
“…43 Enzymes responsible for the metabolism of both methadone isomers include CYP3A4, 2B6, 2C19, 2D6, 2C9, and 3A5. 42,44 Studies demonstrate that patients with homozygous CYP2B6*6 have increased levels of both S-and R-methadone when compared with noncarriers, resulting in a heightened risk for QTc prolongation and other sequelae. [45][46][47] Of note, the CYP2B6*5 allele has been shown to increase CYP2B6 activity because 1 study found lower S-methadone concentrations in patients with the CYP2B6*5 allele.…”
Section: Table 3 (Continued)mentioning
confidence: 99%